The Decline of Nova Scotia Micmac Population, A.D. 1600-1850 - Miller, Virgina P. (Culture, 1982)
This paper traces the decline of the Micmac population of Nova Scotia from A. D. 1600 to its nadir in 1840. It finds the major causes of this decline to be: diseases contracted from Europeans, a genocide campaign conducted by the British, and starvation. The paper then evaluates available population figures for the period 1616-1867 and finds them most reliable for the nineteenth century. Extrapolating back in time, the paper concludes that aboriginal Nova Scotia Micmac population might have been as high as 26,000.